2015
DOI: 10.1111/jfpp.12606
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ajwain (Trachyspermum ammi) Extracted by Ultrasound-Assisted Solvent on Quality Properties of Silver Carp (Hypophthalmichthys molitrix) Surimi Stored at 4C

Abstract: Ultrasound-assisted solvent (UAS) has received considerable attention for the recovery of different compounds from various sources. The aim of this study was to evaluate the UAS of ajwain (Trachyspermum ammi) on the quality of silver carp (Hypophthalmichthys molitrix) surimi. Dried powder of plant seeds were added to ethanol (1: 10 w/v) and extraction was done for 30 min at 45C. The mixture was sonicated at 30 kHz for 15 min at 40C. The extract (0.5% and 0.7% w/w) was mixed with surimi. The control and treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The synthetic antioxidants have been widely used to control lipid oxidative rancidity in foods, which is a major cause of quality deterioration, nutritional losses, off‐flavor development, and discoloration. Besides, prolonging the shelf life of food products, these compounds are able to retard the progress of many oxidative stress‐related chronic diseases in human (Farahmandfar, Safari, Ahmadi Vavsari, & Bakhshandeh, ). Therefore, dietary antioxidants also have an important role as nutraceuticals due to their role in protecting the body from free radicals, reactive oxygen species, and reactive nitrogen species, which are derived either from normal metabolic processes or from external sources (Farhoosh, Johnny, Asnaashari, Molaahmadibahraseman, & Sharif, ).…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic antioxidants have been widely used to control lipid oxidative rancidity in foods, which is a major cause of quality deterioration, nutritional losses, off‐flavor development, and discoloration. Besides, prolonging the shelf life of food products, these compounds are able to retard the progress of many oxidative stress‐related chronic diseases in human (Farahmandfar, Safari, Ahmadi Vavsari, & Bakhshandeh, ). Therefore, dietary antioxidants also have an important role as nutraceuticals due to their role in protecting the body from free radicals, reactive oxygen species, and reactive nitrogen species, which are derived either from normal metabolic processes or from external sources (Farhoosh, Johnny, Asnaashari, Molaahmadibahraseman, & Sharif, ).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations have demonstrated that synthetic antioxidants are toxic and carcinogenic for humans (Iqbal et al 2008). Recently, there has been increased interest in identifying potential sources in order to obtain natural antioxidants (Poiana 2012;Farahmandfar et al 2015b). Essential oil (EO) and extracts from spices, fruits, herbs, and hull contain effective compounds that prevent from the undesirable oxidative process in foodstuff .…”
Section: Introductionmentioning
confidence: 99%
“…This was in accordance with the study of Jafarinia et al (2022) for encapsulated ajowan EO on extending lamb meat shelf life (Jafarinia et al, 2022). Another study by Farahmandfar et al (2016) revealed an inhibitory effect of TPC on TVC of refrigerated fish surimi during storage (Farahmandfar et al, 2016). As shown in the evaluation of the antimicrobial activity test, the CEO had antimicrobial activity.…”
Section: Resultsmentioning
confidence: 98%